2010
DOI: 10.1007/s00011-010-0183-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-O-β-glucoside inhibits LPS-induced expression of inflammatory mediators through decreasing IκBα phosphorylation in THP-1 cells

Abstract: Our results suggest that C3G exerts its anti-inflammatory effect through inhibiting IkappaBalpha phosphorylation, thereby suppressing NF-kappaB activity in THP-1 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 40 publications
3
37
0
1
Order By: Relevance
“…Anthocyanins are abundant in various fruits and vegetables and their related products, including grapes, berries, red cabbage and red wine. Our previous studies, in addition to those of other research groups, have demonstrated that intake of anthocyanin-rich beverages or pure anthocyanins inhibits atherosclerosis through anti-oxidative and anti-inflammatory properties [15], [16], as well as by improving lipid profiles and endothelium-dependent vasodilatation [15], [17][19]. Furthermore, some studies have shown that dietary supplementation with anthocyanins imparts anti-thrombotic effects by modulating platelet aggregation and function in human whole blood and platelet-rich plasma (PRP) [20].…”
Section: Introductionmentioning
confidence: 91%
“…Anthocyanins are abundant in various fruits and vegetables and their related products, including grapes, berries, red cabbage and red wine. Our previous studies, in addition to those of other research groups, have demonstrated that intake of anthocyanin-rich beverages or pure anthocyanins inhibits atherosclerosis through anti-oxidative and anti-inflammatory properties [15], [16], as well as by improving lipid profiles and endothelium-dependent vasodilatation [15], [17][19]. Furthermore, some studies have shown that dietary supplementation with anthocyanins imparts anti-thrombotic effects by modulating platelet aggregation and function in human whole blood and platelet-rich plasma (PRP) [20].…”
Section: Introductionmentioning
confidence: 91%
“…Also U937 pro-monocytes differentiate into mature monocytes or into macrophages upon PMA-treatment. Typical exposure to PMA is for 48 h (Zhang et al 2010 ;Gillies et al 2012 ;Moreno-Navarrete et al 2009 ;Cam and de Mejia 2012 ). The temperature and atmosphere, if described, was the same for each study, namely 37 °C and 5 % CO 2 respectively.…”
Section: Differentiation Of Thp-1 and U937 Monocytes Into Macrophagesmentioning
confidence: 99%
“…The MTT assay was performed as described previously, 20) except that A549 cells were incubated with MTT (500 µg/mL) for the last 4 h of the incubation and that absorbance at 570 nm was measured by iMark microplate reader (Bio-Rad Laboratories, Hercules, CA, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%